2005
DOI: 10.1007/s00198-005-1860-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between 25-hydroxy vitamin D levels, physical activity, muscle strength and fractures in the prospective population-based OPRA Study of Elderly Women

Abstract: Vitamin D supplements have been used to prevent fractures. The effect may be mediated through increased bone mass, but also through reduced falling propensity. The aim of this study was to evaluate the association between 25-hydroxy vitamin D levels (25OHD), fall-associated variables (including tests of functional performance), and fracture in ambulatory women. At baseline 25OHD was measured in 986 women. Fall-associated variables were investigated at baseline. Fractures were recorded during a 3-year follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
251
3
18

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 344 publications
(293 citation statements)
references
References 39 publications
19
251
3
18
Order By: Relevance
“…(10,(16)(17)(18)(19)(20)(21)(22) It has been shown that ambulation time over an 8-ft walkway correlated with higher serum 25(OH)D concentrations. (10,18) Gerdhem and colleagues (19) also have reported a positive significant linear correlation with usual walking speed in a cohort of 986 elderly women. However, this result was less reliable than previous studies because no adjustments for confounders were made.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(10,(16)(17)(18)(19)(20)(21)(22) It has been shown that ambulation time over an 8-ft walkway correlated with higher serum 25(OH)D concentrations. (10,18) Gerdhem and colleagues (19) also have reported a positive significant linear correlation with usual walking speed in a cohort of 986 elderly women. However, this result was less reliable than previous studies because no adjustments for confounders were made.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies used different cutoff values for abnormal serum 25(OH)D concentrations ranging from 10 to 30 ng/mL, (10,(16)(17)(18)(19)(20)(21)(22) which also may explain the divergences. From a historical point of view, normal vitamin D concentrations have been defined by the avoidance of adverse health consequences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations